Peer Supervision as a Collaborative Approach to Improving Teacher Professionalism: A Case Study in a Public Junior High School - Widodo, Sapto; Sumardjoko, Bambang; Muhibbin, Ahmad (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe peer supervision practices, teacher responses, and its contribution to enhancing teacher professionalism at SMP Negeri 1 Kebakkramat. A qualitative approach was employed, collecting data through questionnaires, interviews, and observations with 18 teachers. The findings show that peer supervision is conducted systematically through pre-supervision, implementation, and reflection stages. Teachers responded positively, felt free to share teaching practices, and experienced enhanced collaboration. The collaboration includes joint preparation of teaching materials, development of instructional media, and discussions on classroom management. Peer supervision significantly contributes to improving teacher professionalism, particularly in lesson planning, teaching methods, classroom management, and self-reflection. Challenges include limited time, administrative workload, and varying levels of commitment. Overall, peer supervision is an effective strategy for fostering a culture of professionalism in schools.